Risk factors for neonatal sepsis among neonates in the neonatal intensive care unit at Hawassa University Comprehensive Specialized Hospital and Adare General Hospital in Hawassa City, Ethiopia - Shifera, Nigusie; Dejenie, Filagot; Mesafint, Gebremeskel; Yosef, Tewodros (Frontiers in Pediatrics, 2023)
Background Neonatal sepsis (NS) is a serious blood bacterial infection in children of 28 days or younger, manifested by systemic signs and symptoms of infection. Neonatal sepsis has become one of the leading causes of admission and death in developing countries like Ethiopia. Understanding different risk factors for neonatal sepsis is essential for early diagnosis and treatment. So, this study aimed to assess the risk factors for neonatal sepsis among neonates at Hawassa University Comprehensive Specialized Hospital and Adare General Hospital in Hawassa City, Ethiopia. Methods and materials A case–control study design was employed on 264 neonates (66 cases and 198 controls) in Hawassa University Comprehensive Specialized Hospital and Adare General Hospital from April to June 2018. Data were collected by interviewing the mothers and reviewing neonates’ medical records. The data were edited, cleaned, coded, and entered into Epi info version 7 and were transported and analyzed using SPSS version 20. The odds ratios (ORs) with 95% confidence intervals (CIs) were used to assess the significance of the associations. Result A total of 264 neonates (66 cases and 198 controls) with 100% response rate. The mean (±SD) age of mothers was 26 ± 4.042 years. The majority (84.8%) of the cases were found in children under 7 days, with a mean age of 3.32 days ± 3.376 SD. Factors such as prolonged rupture of the membrane [AOR = 4.627; 95% CI (1.997–10.72)], history of the urinary tract or sexually transmitted infections [AOR = 2.5; 95% CI (1.151–5.726)], intrapartum fever [AOR = 3.481; 95% CI (1.18–10.21)], foul smelling liquor [AOR = 3.64; 95% CI (1.034–12.86)], and low APGAR score in the fifth minute [AOR = 3.38; 95% CI (1.107–10.31)] were the independent predictors of neonatal sepsis. Conclusion Prolonged rupture of the membrane, intrapartum fever, urinary tract infection, foul-smelling liquor, and low APGAR score were independent risk factors of neonatal sepsis, and this study also observed that the onset of neonatal sepsis was higher in the first week of a neonate's life. Routine sepsis evaluation must focus on neonates born with the aforementioned characteristics and make interventions for babies born with these risk factors.